The Manila Synod of 1582 the draft of its handbook for confessors - Salazar, Domingo de; Dumol, Paul Arvisu 1951-; Ateneo de Manila University Press (Quezon City Ateneo de Manila University Press, 2014)
"In 1582 Domingo de Salazar, the first bishop of the Philippines, alarmed by reports from Filipinos themselves on the abuses they were suffering at the hands of Spanish officials and soldiers, convoked what has come to be known as the first Synod of Manila. The assembly identified all the different ways Filipinos were being oppressed and determined the cases in which restitution had to be made and how much. All this was set down in a handbook for confessors."--Provided by publisher.
Includes bibliographical references and index.
English translation of the author's original Spanish work.
Keywords: Catholic Church. -- Archdiocese of Manila (Philippines). -- Sínodo -- (1582).; Philippines -- History -- 1521-1812 -- Sources; Philippines -- Church history -- Sources